The impact of stony coral tissue loss disease and amoxicillin treatments on coral gametogenesis - Hannah E. Mazurek; Karen L. Neely; D. Abigail Renegar (Frontiers in Marine Science)
The unprecedented mortality of stony corals on Florida’s Coral Reef from stony coral tissue loss disease (SCTLD) was mitigated on some priority sites and corals through the use of a topical amoxicillin paste to halt disease lesion progression. One management concern about the use of antibiotics on these corals was the impact it may have on gametogenesis. We used histology to assess gametogenesis within Orbicella faveolata and Montastraea cavernosa samples from six sites and across three treatment groups. The sites covered the geographic regions of the Florida Keys, including both inshore and offshore habitats. The treatment groups were: healthy corals, samples adjacent to active SCTLD lesions, and samples adjacent to previous SCTLD lesions that were halted by topical amoxicillin. Across both species, colonies from all sites and treatment groups were producing normal oocytes and spermaries. For M. cavernosa, gametogenesis metrics did not differ among treatment groups. Among O. faveolata colonies, healthy corals exhibited higher fecundity and higher oocyte presence than treated corals and larger oocytes than diseased corals. However, of the treated corals, those which had been treated more frequently had higher fecundity than those that were treated less frequently, suggesting that diminished fecundity throughout the group may have been the result of disease occurring earlier in gametogenesis rather than the treatment itself. Fecundity of O. faveolata colonies in the diseased group was highly dependent on whether the corals were from nearshore or offshore environments. The relationship between disease, treatment, and habitat warrants further examination, but we show that amoxicillin treatments do not prevent gametogenesis in corals.